Preservaçao do patrimônio documental arquivístico em ambiente digital - Santos, Henrique Machado (Palabra Clave.)
This article pervades the idea of the digital record as an integral part of the cultural heritage, and later, it describes pertinent aspects to its preservation. For this, issues related to guaranteeing access to authentic records in the long term are addressed. The discussion focuses on the relationship between preservation strategies, digital repositories, OAIS model, uninterrupted custody line, and audit and certification activities. Among the final notes, it is necessary to synthesize the knowledge discussed in order to provide theoretical subsidies to facilitate its application in the archival science